PREGNANT WOMEN'S RECOLLECTIONS OF EARLY MATERNAL BONDING: ASSOCIATIONS WITH MATERNAL–FETAL ATTACHMENT AND BIRTH CHOICES. Issue 5 (6th August 2018) - Handelzalts, Jonathan E.; Preis, Heidi; Rosenbaum, Maya; Gozlan, Miri; Benyamini, Yael
ABSTRACT: Recollections of own maternal care measured by parental bonding were found to be important in the pregnant woman's construction of herself as a mother. Although these recollections were studied with regard to various variables, there is a dearth of studies associated with pregnancy and childbirth. In this cross‐sectional study, 341 pregnant women were recruited. Measures included a Sociodemographics–Obstetric History Questionnaire; the Childbirth Choices Questionnaire (H. Preis, M. Gozlan, U. Dan, & Y. Benyamini, 2018); the Parental Bonding Instrument (G. Parker, H. Tupling, & L.B. Brown, 1979); a question regarding the planned presence of the woman's mother at delivery; and the Maternal‐Fetal Attachment Scale (M.S. Cranley, 1981). Parental recollections of Care were associated with fewer natural birth choices (hence, a more "medicalized" delivery), lower maternal–fetal attachment, and a wish for the mother's mother to be present at the birth. Parental recollections of Encouragement of Behavioral Freedom in childhood were associated with more natural choices regarding childbirth. In addition, women with higher scores on the parental bonding Denial of Autonomy factor reported stronger maternal–fetal attachment. Thus, early recollections of experiences with caregivers as manifested in parental bonding may be a possible influence on the transition to motherhood, and working through possible difficulties associated with these recollections may improve adjustment to motherhood.